2021
DOI: 10.1186/s12920-020-00864-0
|View full text |Cite
|
Sign up to set email alerts
|

ShareDNA: a smartphone app to facilitate family communication of genetic results

Abstract: Background Genetic testing allows patients and clinicians to understand the risk of hereditary diseases. By testing early, individuals can make informed medical decisions about management which may minimize the risk of developing certain diseases. Importantly, genetic test results may also be applicable to patients’ biological relatives; thus, these results could also lead to minimizing their risk of disease. However, sharing genetic test results between patients and their relatives is scarce. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…However, ongoing studies, such as the IMPACT-FH (Identification Methods, Patient Activation, and Cascade Testing for FH) study ( Campbell-Salome et al, 2021 ), are exploring strategies that increase the uptake of cascade testing in population-based screening programs. However, learnings from the diagnostic setting may provide some insights, including the availability of clinician-drafted letters ( Newson and Humphries, 2005 ; Suthers et al, 2006 ; Hadfield et al, 2009 ; Dilzell et al, 2014 ; Petersen et al, 2019 ; Kurian and Katz, 2020 ; Neuner et al, 2020 ), access to support from foundations focused on a single condition or clinical area ( Bell et al, 2015 ; Wald et al, 2016 ; McGowan et al, 2021 ), and access to educational materials that are easily shared outside of a clinical setting ( Kardashian et al, 2012 ; Petersen et al, 2019 ; Bowen et al, 2020 ; Jujjavarapu et al, 2021 ; Nazareth et al, 2021 ; Nitecki et al, 2021 ; Snir et al, 2021 ). When considering approaches to encouraging at-risk relatives to ultimately seek cascade testing, programs have been designed to offer cascade testing at reduced rates or at no-charge for relatives ( Aktan-Collan et al, 2007 ; Caswell-Jin et al, 2019 ; Courtney et al, 2019 ; Invitae, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, ongoing studies, such as the IMPACT-FH (Identification Methods, Patient Activation, and Cascade Testing for FH) study ( Campbell-Salome et al, 2021 ), are exploring strategies that increase the uptake of cascade testing in population-based screening programs. However, learnings from the diagnostic setting may provide some insights, including the availability of clinician-drafted letters ( Newson and Humphries, 2005 ; Suthers et al, 2006 ; Hadfield et al, 2009 ; Dilzell et al, 2014 ; Petersen et al, 2019 ; Kurian and Katz, 2020 ; Neuner et al, 2020 ), access to support from foundations focused on a single condition or clinical area ( Bell et al, 2015 ; Wald et al, 2016 ; McGowan et al, 2021 ), and access to educational materials that are easily shared outside of a clinical setting ( Kardashian et al, 2012 ; Petersen et al, 2019 ; Bowen et al, 2020 ; Jujjavarapu et al, 2021 ; Nazareth et al, 2021 ; Nitecki et al, 2021 ; Snir et al, 2021 ). When considering approaches to encouraging at-risk relatives to ultimately seek cascade testing, programs have been designed to offer cascade testing at reduced rates or at no-charge for relatives ( Aktan-Collan et al, 2007 ; Caswell-Jin et al, 2019 ; Courtney et al, 2019 ; Invitae, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings underscore the need for novel methods for disseminating genetic risk information in families and equipping relatives to act on this information. Numerous studies have investigated the acceptability and utility of direct‐contact methods and technology interventions to assist with cascade screening (Haas et al, 2021; Jujjavarapu et al, 2021; Schmidlen et al, 2019; Sturm, 2016), and such approaches should continue to be explored. Although not specifically analyzed in this review, we identified five studies demonstrating the cost‐effectiveness of genetic testing and cascade screening for HCM, derived from cessation of cardiac screening for genotype‐negative relatives.…”
Section: Discussionmentioning
confidence: 99%
“…ogy interventions to assist with cascade screening(Haas et al, 2021;Jujjavarapu et al, 2021;Schmidlen et al, 2019;Sturm, 2016), and such approaches should continue to be explored. Although not specifically analyzed in this review, we identified five studies demonstrating the cost-effectiveness of genetic testing and cascade screening for HCM, derived from cessation of cardiac screening for genotype-negative relatives.…”
mentioning
confidence: 99%
“…who communicate with each other for conducting group services. DNAbased U-healthcare includes various services, namely, disease virus control, body fluid monitoring, blood-based prognostic tracking, and so on [3,40]. Taking family healthcare services as an example, multiple members P i in a family may request a common DNA-based healthcare service provided by S j .…”
Section: System Model and Adversarial Capabilitiesmentioning
confidence: 99%